Cellular and molecular alterations in neurons and glial cells in inherited retinal degeneration - Martínez-Gil, Natalia; Maneu, Victoria; Kutsyr, Oksana; Fernández-Sánchez, Laura; Sánchez-Sáez, Xavier; Sánchez-Castillo, Carla; Campello, Laura; Lax, Pedro; Pinilla, Isabel; Cuenca, Nicolás (Frontiers in Neuroanatomy, 2022)
Multiple gene mutations have been associated with inherited retinal dystrophies (IRDs). Despite the spectrum of phenotypes caused by the distinct mutations, IRDs display common physiopathology features. Cell death is accompanied by inflammation and oxidative stress. The vertebrate retina has several attributes that make this tissue vulnerable to oxidative and nitrosative imbalance. The high energy demands and active metabolism in retinal cells, as well as their continuous exposure to high oxygen levels and light-induced stress, reveal the importance of tightly regulated homeostatic processes to maintain retinal function, which are compromised in pathological conditions. In addition, the subsequent microglial activation and gliosis, which triggers the secretion of pro-inflammatory cytokines, chemokines, trophic factors, and other molecules, further worsen the degenerative process. As the disease evolves, retinal cells change their morphology and function. In disease stages where photoreceptors are lost, the remaining neurons of the retina to preserve their function seek out for new synaptic partners, which leads to a cascade of morphological alterations in retinal cells that results in a complete remodeling of the tissue. In this review, we describe important molecular and morphological changes in retinal cells that occur in response to oxidative stress and the inflammatory processes underlying IRDs.